Budaya dan Kualitas Kerja pada Perusahaan Manufaktur dan Eksportir Rotan - Rudy Aryanto; Syam Rizma (Bina Nusantara University, 2009)
Cane (Calamus spp), also known as rattan, is an important non-timber forest product used extensively all over Indonesia as a raw material for making furniture, handicraft, and other household articles. The study aims to generate information on production and export industry of rattan furniture, identify problems, and recommend solutions. The general problem on rattan manufacture management is human resources especially working ethos and performance of employees. The aim of this research is to analyze the influence of quality management and working ethos towards working performance of the employee at a rattan exporter and industry. Analysis method used are associative and Pearson correlation. The data collected from the employee towards quality management and working ethos, by filling out the questionnaire provided by using Likert scale that is effective to analyze the composition of the agreement and disagreement towards the statement on the questionnaire. The result achieved from this research is to learn the relation between quality management of working ethos, notify the relation between quality management and working ethos with working performance, and acknowledge the influence between quality management and working ethos, and working performance. The quality management has a low relation towards working performance. Working ethos has a strong relation with working performance. Quality management and working ethos has a strong relation towards working performance employees in rattan exporter and industry.